A novel R3 MYB transcriptional repressor, MaMYBx, finely regulates anthocyanin biosynthesis in grape hyacinth. (September 2020) - Zhang, Han; Gong, Jiaxin; Chen, Kaili; Yao, Wenkong; Zhang, Boxiao; Wang, Jiangyu; Tian, Shuting; Liu, Hongli; Wang, Yanqing; Liu, Yali; Du, Lingjuan
Highlights: A R3-MYB repressor, MaMYBx, was isolated from grape hyacinth ( Muscari spp.). MaMYBx temporal expression pattern was correlated with anthocyanin accumulation during flower development. MaMYBx was activated by MaMybA alone or by MaMybA/MaAN2 and cofactor MabHLH1. MaMYBx suppressed its own activation and that of MaMybA promoters mediated by MaMybA/MaAN2 and MabHLH1. MaMYBx finely regulates anthocyanin biosynthesis by binding to MabHLH1 and disrupting the R2R3 MYB-bHLH complex. Abstract: R3-MYBs negatively regulate anthocyanin pigmentation in plants. However, how R3-MYB repressors finely modulate anthocyanin biosynthesis in cooperation with R2R3-MYB activators remains unclear in monocots. We previously identified two anthocyanin-related R2R3-MYB activators (MaMybA and MaAN2) in grape hyacinth ( Muscari spp.). Here, we isolated a R3-MYB repressor, MaMYBx, and characterized its role in anthocyanin biosynthesis using genetic and biochemical markers. The temporal expression pattern of MaMYBx was similar to that of MaMybA and MaAN2, and it was correlated with anthocyanin accumulation during flower development. MaMYBx could be activated either by MaMybA alone or by MaMybA/MaAN2 and cofactor MabHLH1, and it suppressed its own activation and that of MaMybA promoters mediated by MaMybA/MaAN2 and MabHLH1. Like MaMybA, MaMYBx interacted with MabHLH1. MaDFR and MaANS transcription and anthocyanin accumulation mediated by MaMybA/MaAN2 and MabHLH1 were inhibited by MaMYBx. Overexpression of MaMYBx in tobacco greatly reduced flower pigmentation and repressed the expression of late structural and regulatory anthocyanin pathway genes. Thus, MaMYBx finely regulates anthocyanin biosynthesis by binding to MabHLH1 and disrupting the R2R3 MYB-bHLH complex in grape hyacinth. The regulatory network of transcriptional activators and repressors modulating anthocyanin biosynthesis is conserved within monocots. MaMYBx seems a potentially valuable target for flower color modification in ornamental plants.